INTERVENSI PSIKOLOGIS PADA PENDIDIKAN ANAK DENGAN KETERLAMBATAN BICARA - Habib, Zainal; Hidayati, Laily (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
As the ability to ride a bike, speech is a child's ability to learn. The more frequent practice, these abilities will be more perfect. Many factors affect the process of learning or practice speaking. Among others is the maturity or physical and mental readiness, a good model to be emulated, the motivation they need, the opportunities provided by the environment, and the existence guidance of significant others. Then, how to help children who have spent time to learn speech and due to several factors as mentioned above, have experienced delays in speech?. Excavation data about the causes of overdue talking to children, followed by the deepening problems in a mature, will find the steps that can be taken to help overdue talking children in speech.